1, 3, 4‐oxadiazole derivatives as potential antimicrobial agents. (27th June 2022) - Tiwari, Deeksha; Narang, Rakesh; Sudhakar, Kalvatala; Singh, Vikramjeet; Lal, Sukhbir; Devgun, Manish
Abstract: Due to the emergence of drug‐resistant microbial strains, different research groups are continuously developing novel drug molecules against already exploited and unexploited targets. 1, 3, 4‐Oxadiazole derivatives exhibited noteworthy antimicrobial activities. The presence of 1, 3, 4‐oxadiazole moiety in antimicrobial agents can modify their polarity and flexibility, which significantly improves biological activities due to various bonded and non‐bonded interactions viz. hydrogen bond, steric, electrostatic, and hydrophobic with target sites. The present review elaborates the therapeutic targets and mode of interaction of 1, 3, 4‐oxadiazoles as antimicrobial agents. 1, 3, 4‐oxadiazole derivatives target enoyl reductase (InhA), 14α‐demethylase in the mycobacterial cell; GlcN‐6‐P synthase, thymidylate synthase, peptide deformylase, RNA polymerase, dehydrosqualene synthase in bacterial strains; ergosterol biosynthesis pathway, P450‐14α demethylase, protein‐N‐myristoyltransferase in fungal strains; FtsZ protein, interfere with purine and functional protein synthesis in plant bacteria. The present review also summarizes the effect of different moieties and functional groups on the antimicrobial activity of 1, 3, 4‐oxadiazole derivatives. Abstract : 1, 3, 4‐oxadiazole derivatives can target enoyl reductase, 14‐α‐demethylase in the mycobacterial cell; GlcN‐6‐P synthase, thymidylate synthase, biofilm, peptide deformylase, RNA polymerase, dehydrosqualene synthase in bacterial strains; ergosterol biosynthesis pathway, P−450‐14α demethylase in fungal strains. 1, 3, 4‐Oxadiazole derivatives also exhibited insecticidal activities against plant pathogens by interfering with the functioning of ribosomes. The effect of various substituents attached to 1, 3, 4‐oxadiazole derivatives on different antimicrobial activities has been analyzed.